Peluang Dan Tantangan Perbankan Syariah Di Indonesia Pasca Merger - Putra, Pulun Pradana; Febriati, Nurullia (Universitas Islam Negeri Raden Intan Lampung, 2021)
The development of sharia banks in Indonesia is very rapid, the latest three sharia banks owned by the Association of State-Owned Banks (Himbara) namely PT Bank BRISyariah Tbk (BRIS), PT Bank Syariah Mandiri (BSM), and PT Bank BNI Syariah (BNIS) merged into Bank Syariah Indonesia (BSI). However, the existence of sharia banks and the merger of three banks into BSI have not been fully responded positively by the market. Some Indonesians, especially Muslims have not made sharia banks a reference, not even infrequently they prefer to use conventional banks. In fact, in its system, BSI refers to sharia principles that guarantee its halalness and away from ribawi systems and practices. This study uses the library study method. This study concluded that BSI has a great opportunity in improving the economy of Indonesian people. BSI can improve the competitiveness of Sharia finance in the digital age. BSI has many opportunities to progress because many components support the creation of superior and reliable Sharia banking. BSI has enough power to advance to become a leading bank that plays an important role in economic growth in the country. On the other hand, BSI also faces challenges, namely the lack of institutional development, socialization and promotion, the quality of human resources and the utilization of technology.Keywords : Islamic Bank, Economic Growth, Indonesia